MORFOLOGI JAMUR PEMBENTUK MIKORIZA PADA AKAR RUMPUT - INDIARTO, SUCIATMIH Y. (BERITA BIOLOGI, 1987)
SUCIATMIH Y.INDIARTO.1987.Morphology of mycorrhizal fungi in grass roots.Suppl.Berita Biologi 3 : 26 - 30.Visual examination of roots of grass species collected from the surrounding of Herbarium Bogoriense building and Baranangsiang has shown that the main infecting organisme are Phycomycete endophytes of the vesicular arbuscular type.It was attempted to assess morphology of fungi in the grass roots.External mycelium displays dimorphism. There are thick walled asceptate hyphae and thin-walled septate External vesicles may be formed singly and are sometimes furnished with a rudimentary hyphae Root penetration takes place by hyphae entering either epidermal cells or root hairs.The internal mycelia in grasses correspond to descriptions of similar endophytes in other plants. Internal vesicles are formed mainly in the outer cortical cell layers.In general, these are located both in interaeellular and intercellular position.Internal arbuscules are usually developed in the inner cortical cells.Each cell becomes occupied by an arbuscule.